A Series of Iron(II)‐NHC Sensitizers with Remarkable Power Conversion Efficiency in Photoelectrochemical Cells. Issue 65 (13th October 2021) - Marri, Anil Reddy; Marchini, Edoardo; Cabanes, Valentin Diez; Argazzi, Roberto; Pastore, Mariachiara; Caramori, Stefano; Bignozzi, Carlo Alberto; Gros, Philippe C.
Abstract: A series of six new Fe(II)NHC‐carboxylic sensitizers with their ancillary ligand decorated with functions of varied electronic properties have been designed with the aim to increase the metal‐to‐ surface charge separation and light harvesting in iron‐based dye‐sensitized solar cells (DSSCs). ARM130 scored the highest efficiency ever reported for an iron‐sensitized solar cell (1.83 %) using Mg 2+ and NBu4 I‐based electrolyte and a thick 20 μm TiO2 anode. Computational modelling, transient absorption spectroscopy and electrochemical impedance spectroscopy (EIS) revealed that the electronic properties induced by the dimethoxyphenyl‐substituted NHC ligand of ARM130 led to the best combination of electron injection yield and spectral sensitivity breadth. Abstract : A Fe(II)NHC sensitizer bearing a dimethoxyphenyl group on the ancillary ligand scored the highest efficiency ever reported for an iron‐sensitized solar cell (1.83 %) using Mg 2+ and NBu4 I‐based electrolyte and a thick 20 μm TiO2 anode.